Factors Influencing Earnings Management in Railway Companies in Asia Pacific Region - Romadani, Meina; Aryani, Y Anni (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2021)
This study focuses on the factors that affect Earning Management in railway companies throughout the Asia Pacific, especially bonus plans, leverage, and government subsidies. These three factors are closely related to the characteristics possessed by the railway company. This research is quantitative using secondary data from the annual financial reports of railway companies in the Asia Pacific region from 2010 - 2019 with a sample size of 171 financial reports. The sampling technique was carried out using purposive sampling method. Modified Jones Model is used to measure earnings management. To test the hypothesis in this study using panel data regression analysis using the E-views 9 program. The results showed that the bonus plan has no effect on earning management. Leverage and government subsidies have a negative effect on earning management. Government subsidies have a positive effect on earnings management